2011
DOI: 10.1016/j.resp.2011.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Exercise intolerance at high altitude (5050m): Critical power and W′

Abstract: a b s t r a c tThe relationship between work rate (WR) and its tolerable duration (t LIM ) has not been investigated at high altitude (HA). At HA (5050 m) and at sea level (SL), six subjects therefore performed symptomlimited cycle-ergometry: an incremental test (IET) and three constant-WR tests (% of IET WR max , HA and SL respectively: WR 1 70 ± 8%, 74 ± 7%; WR 2 86 ± 14%, 88 ± 10%; WR 3 105 ± 13%, 104 ± 9%). The power asymptote (CP) and curvature constant (W ) of the hyperbolic WR-t LIM relationship were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 46 publications
(75 reference statements)
6
22
1
Order By: Relevance
“…Equation (5.17) provides the theoretical basis explaining several observations about _ w cr . The fact that the _ w cr = _ w max ratio (i) is higher in athletes with elevated _ V O 2max (Heubert et al 2005) than in subjects with low _ V O 2max (Adami et al 2013), (ii) increases with aerobic training (Heubert et al 2003;Jenkins and Quigley 1992) and high-intensity interval training (Gaesser and Wilson 1988) and (iii) decreases in hypoxia (Dekerle et al 2012;Valli et al 2011) is fully coherent with Eq. (5.17).…”
Section: The Relationship Between _ V O 2max Critical Power and Maxsupporting
confidence: 65%
See 1 more Smart Citation
“…Equation (5.17) provides the theoretical basis explaining several observations about _ w cr . The fact that the _ w cr = _ w max ratio (i) is higher in athletes with elevated _ V O 2max (Heubert et al 2005) than in subjects with low _ V O 2max (Adami et al 2013), (ii) increases with aerobic training (Heubert et al 2003;Jenkins and Quigley 1992) and high-intensity interval training (Gaesser and Wilson 1988) and (iii) decreases in hypoxia (Dekerle et al 2012;Valli et al 2011) is fully coherent with Eq. (5.17).…”
Section: The Relationship Between _ V O 2max Critical Power and Maxsupporting
confidence: 65%
“…It seems logical to expect a decrease in _ w cr after prolonged bed rest, especially during upright exercise, but I am unaware of any study specifically addressing this issue. Conversely, there is some evidence that _ w cr goes down in hypoxia (Dekerle et al 2012;Moritani et al 1981;Parker-Simpson et al 2014;Valli et al 2011). Possibly for its effects on muscle blood flow, and thus on the rate of lactate accumulation, prior high-intensity exercise displaces _ w cr closer to _ w max and reduces W′ (Ferguson et al 2007(Ferguson et al , 2010Miura et al 2009;Vanhatalo and Jones 2009).…”
Section: Descriptive Physiology Of Critical Power and Energy Store Comentioning
confidence: 99%
“…The task-specific nature of W′ was well-exposed in the work of Valli et al (95), who investigated power-duration parameters in cycling, during and after ascent to the Italian National Research Council Pyramid Laboratory, Lobuche, Khumbu, Nepal located at an altitude of 5,050 m. Repeated constant power cycle ergometer exercise tests to intolerance at sea level and high altitude revealed that high-altitude depressed CP by 35%: unsurprising considering the dependence of CP on O 2 delivery and utilization (see “ The Role of Oxygen in Shaping the Power-Duration Curve ” above). The unexpected finding was that W′ decreased at high-altitude, by an average of 45%.…”
Section: Unraveling the Power-duration Curvature Constant (W′) In Heamentioning
confidence: 96%
“…This reduction in W′ was at odds with the expected effects of exposure to acute hypoxia at sea level (62,104), although more recent studies have corroborated this finding (85). Valli et al (95) point out that oxygen stores (predominantly in the form of muscle venous O 2 concentration) are typically notionally lumped within the proposed volume of anaerobic energy stores represented by W′, because they are not measured by pulmonary gas exchange. Therefore W′ may be reduced at altitude because of a reduced capacity of ‘anaerobic’ sources of stored energy.…”
Section: Unraveling the Power-duration Curvature Constant (W′) In Heamentioning
confidence: 99%
“…It seems logical to expect a decrease in _ w cr after prolonged bed rest, especially during upright exercise, but I am unaware of any study specifically addressing this issue. Conversely, there is some evidence that _ w cr goes down in hypoxia (Dekerle et al 2012;Moritani et al 1981;Parker-Simpson et al 2014;Valli et al 2011). Possibly for its effects on muscle blood flow, and thus on the rate of lactate accumulation, prior high-intensity exercise displaces _ w cr closer to _ w max and reduces W′ (Ferguson et al , 2010Miura et al 2009;Vanhatalo and Jones 2009).…”
Section: Abbreviations and Symbolsmentioning
confidence: 99%